Characteristics of Photosynthetic Performance, Antioxidant Capacity and Nutrient Concentration of Tibetan Wild Barley in Response to Aluminium Stress - Dai, Huaxin; Ibrahim, Wasim; Zheng, Wei-Te; Dawood, Muhammad; He, Xiaoyan; Zhao, Jing; Zhang, Guo-Ping; Li, Chengdao; Wu, Fei-Bo (Asian Journal of Chemistry, 2013)
Greenhouse hydroponic experiments were conducted to investigate genotypic differences in response to aluminium stress among two contrasting Tibetan wild barley genotypes XZ16 (aluminium tolerant) and XZ61 (aluminium sensitive) and cv. Dayton (aluminium tolerant) and as affected by anion inhibitor of niflumic acid (NIF). The results showed that Tibetan wild barley XZ16 exhibited superior aluminium-resistantce/tolerance reflected by significant low aluminium uptake and malondialdehyde (MDA) accumulation and an enhancement in net photosynthetic rate, stomatal conductance, transpiration rate and maintaining relatively lower intercellular CO2 concentration (Ci) under 100 μM aluminium in contrast to XZ61 and Dayton. Meanwhile, XZ16 exhibited higher P, S, Ca and Mg contents in roots and shoots under aluminium stress compared with XZ61 and Dayton. Moreover, activities of catalase (CAT) andascorbate peroxidase (APX) in ROS scavenging systems play an important role in alleviating aluminium induced oxidative stress in XZ16. Shoot CAT in XZ16 was markedly enhanced after 15 d aluminium treatment, while markedly reduced in XZ61. APX of XZ16 showed special changing pattern against the other two genotypes i.e. root/shoot APX increased after 6 h aluminium treatment and niflumic acid (Al + NIF) significantly enhanced shoot APX activity in XZ16, but not in XZ61 and Dayton. After 10 days aluminium exposure, shoot APX in XZ16 was kept similar value to its control, but in XZ61 and Dayton was sharply reduced relative to controls.